2022
DOI: 10.3390/ijms23042098
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ligand-Mimetic and Nonmimetic Inhibitors of the Ceramide Transport Protein CERT

Abstract: Lipid transfer proteins (LTPs) are recognized as key players in the inter-organelle trafficking of lipids and are rapidly gaining attention as a novel molecular target for medicinal products. In mammalian cells, ceramide is newly synthesized in the endoplasmic reticulum (ER) and converted to sphingomyelin in the trans-Golgi regions. The ceramide transport protein CERT, a typical LTP, mediates the ER-to-Golgi transport of ceramide at an ER-distal Golgi membrane contact zone. About 20 years ago, a potent inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 124 publications
(209 reference statements)
0
6
0
Order By: Relevance
“…We previously developed two types of potent CERT inhibitors: (1 R ,3 S )-HPA-12, a ceramide mimetic compound [ 16 , 17 ], and E16A (also known as (1 S ,2 R )-HPCB-5), a ceramide nonmimetic compound ( Figure 1 ) [ 18 ]. HPA-12 has two chiral carbons comprising four stereoisomers ( Figure 1 ); only the (1 R ,3 S )-configuration exhibits potent CERT inhibition activity [ 16 , 19 , 20 , 21 ]. Notably, the initial assigned configuration of active HPA-12 [ 16 , 22 ] was later revised to (1 R ,3 S ) [ 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously developed two types of potent CERT inhibitors: (1 R ,3 S )-HPA-12, a ceramide mimetic compound [ 16 , 17 ], and E16A (also known as (1 S ,2 R )-HPCB-5), a ceramide nonmimetic compound ( Figure 1 ) [ 18 ]. HPA-12 has two chiral carbons comprising four stereoisomers ( Figure 1 ); only the (1 R ,3 S )-configuration exhibits potent CERT inhibition activity [ 16 , 19 , 20 , 21 ]. Notably, the initial assigned configuration of active HPA-12 [ 16 , 22 ] was later revised to (1 R ,3 S ) [ 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…HPA-12 has two chiral carbons comprising four stereoisomers ( Figure 1 ); only the (1 R ,3 S )-configuration exhibits potent CERT inhibition activity [ 16 , 19 , 20 , 21 ]. Notably, the initial assigned configuration of active HPA-12 [ 16 , 22 ] was later revised to (1 R ,3 S ) [ 19 , 20 , 21 ]. A racemic mixture of (1 R ,3 R )/(1 S ,3 S )-HPA-12 (hereafter abbreviated as HPA-12-IR) is a control that lacks CERT inhibitory activity ( Figure 1 and Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…POGL structurally resembles ceramide and is produced as a byproduct in the synthesis of sphingomyelin wherein the phosphorylcholine head is transferred from phosphatidylcholine to ceramide, liberating POGL. It has been shown that the CERT START can transfer short-chain diacylglycerol (C10-DAG) in vitro but with a lower efficiency (only 5%) of the ceramide suggesting that CERT might mediate Golgi-to-ER trafficking of DAG in exchange for ER-to-Golgi trafficking of ceramide ( 46 , 47 ). In our simulation the POGL lipid does not remain in the cavity for long.…”
Section: Discussionmentioning
confidence: 99%
“…It also helps differentiate on and off target effects when CERT is pharmacologically inhibited. [ 97 ] …”
Section: Mcs In Therapeuticsmentioning
confidence: 99%